Graphene mode-locked ultrafast laser. - Sun,Z; Hasan,T; Torrisi,F; Popa,D; Privitera,G; Wang,F; Bonaccorso,F; Basko,DM; Ferrari,AC (ACS Nano, 2010)
Graphene is at the center of a significant research effort. Near-ballistic transport at room temperature and high mobility make it a potential material for nanoelectronics. Its electronic and mechanical properties are also ideal for micro- and nanomechanical systems, thin-film transistors, and transparent and conductive composites and electrodes. Here we exploit the optoelectronic properties of graphene to realize an ultrafast laser. A graphene-polymer composite is fabricated using wet-chemistry techniques. Pauli blocking following intense illumination results in saturable absorption, independent of wavelength. This is used to passively mode-lock an erbium-doped fiber laser working at 1559 nm, with a 5.24 nm spectral bandwidth and approximately 460 fs pulse duration, paving the way to graphene-based photonics.